EFFECTS OF PROCESSING ON THE PROXIMATE AND MINERAL COMPOSITION OF CULTURED AND CAPTURED CLARIAS GARIEPPINUS - Oyekanmi, Funmilayo Bosede; Ekundare, Olugbemi Victor; Oyekanmi, Oluwatomisin Adediji (FUDMA Journal of Sciences, 2024)
Fish and fish products serve as vital protein sources in Africa and the world in general. Since fish is typically processed before consumption, this study investigated how different processing methods affect the proximate and mineral composition of both cultured and captured Clarias gariepinus. The processing techniques employed in this research included smoking, boiling, and oven drying. Cultured catfish were sourced from Oris Farm in Osogbo, Osun State, Nigeria, while captured catfish were obtained from Asejire Dam in Oyo State. The proximate and mineral compositions of fresh, boiled, smoked, and oven-dried samples of both cultured and captured Clarias gariepinus were analyzed in triplicate. The results indicated significant differences (P
Keywords: Proximate; Mineral; Processing; Clarias gariepinus